Pembentukan karakter melalui pendidikan agama Islam - Billah, Ahmad Nastain (Maliki Interdisciplinary Journal, 2024)
Islamic religious education plays an important role in shaping a person's character. One of the most important components in character education is Islamic Religious Education (PAI). Instilling a religious soul in children is the first step towards the success of a character education program. The approach used in this study is the theoretical approach method. Researchers can assess and study the contribution of journals to current theoretical knowledge by using a theoretical framework. The results of this study show that the formation of student character is greatly assisted by Islamic religious education. Producing dignified, polite, and helpful people is the goal to be achieved. If religious values ​​are instilled from an early age, then a generation of successors will be born who are noble, wise, and obedient to God. Therefore, Islamic religious education in schools is very important to help students develop their morals. Islamic Religious Education is very important to be taught in schools to foster students' morals and uphold the importance of character education for children.